Novel XBP1s-independent function of IRE1 RNase in HIF-1α-mediated glycolysis upregulation in human macrophages upon stimulation with LPS or saturated fatty acid - Iovino, Margaud; Colonval, Megan; Wilkin, Chloé; L’homme, Laurent; Lassence, Cédric; Campas, Manon; Peulen, Olivier; de Tullio, Pascal; Piette, Jacques; Legrand-Poels, Sylvie (Frontiers in Immunology, 2023)
In obesity, adipose tissue infiltrating macrophages acquire a unique pro-inflammatory polarization, thereby playing a key role in the development of chronic inflammation and Type 2 diabetes. Increased saturated fatty acids (SFAs) levels have been proposed to drive this specific polarization. Accordingly, we investigated the immunometabolic reprogramming in SFA-treated human macrophages. As expected, RNA sequencing highlighted a pro-inflammatory profile but also metabolic signatures including glycolysis and hypoxia as well as a strong unfolded protein response. Glycolysis upregulation was confirmed in SFA-treated macrophages by measuring glycolytic gene expression, glucose uptake, lactate production and extracellular acidification rate. Like in LPS-stimulated macrophages, glycolysis activation in SFA-treated macrophages was dependent on HIF-1α activation and fueled the production of pro-inflammatory cytokines. SFAs and LPS both induced IRE1α endoribonuclease activity, as demonstrated by XBP1 mRNA splicing, but with different kinetics matching HIF-1α activation and the glycolytic gene expression. Interestingly, the knockdown of IRE1α and/or the pharmacological inhibition of its RNase activity prevented HIF-1α activation and significantly decreased glycolysis upregulation. Surprisingly, XBP1s appeared to be dispensable, as demonstrated by the lack of inhibiting effect of XBP1s knockdown on glycolytic genes expression, glucose uptake, lactate production and HIF-1α activation. These experiments demonstrate for the first time a key role of IRE1α in HIF-1α-mediated glycolysis upregulation in macrophages stimulated with pro-inflammatory triggers like LPS or SFAs through XBP1s-independent mechanism. IRE1 could mediate this novel function by targeting other transcripts (mRNA or pre-miRNA) through a mechanism called regulated IRE1-dependent decay or RIDD. Deciphering the underlying mechanisms of this novel IRE1 function might lead to novel therapeutic targets to curtail sterile obesity- or infection-linked inflammation.